Aphid Atraction to Various Mosaic Viruses - Nguyen, Valerie; Klein, Peter; Smith, Michael (My University, 2017)
Aphids are the most common vectors of plant viruses known, and mosaic viruses are easily spread through them [2]. Corn leaf aphids (Rhopalosiphum maidis) can be found nearly worldwide, effecting corn and wild cereal growth. Mosaic viruses effect an array of plants, such as sorghum (Sorghum bicolor), one of Kansas’ main crop produced. These viruses can cause necrosis in the foliage, and can reduce yields. The Potyviruses tested in this experiment were Sugarcane Mosaic Virus, Maize Dwarf Mosaic Virus, Sorghum Mosaic Virus, and Johnsongrass Mosaic Virus . With over 100 different species, Potyviruses are the largest genus ssRNA plant viruses transmitted in a non persistent manner by their vectors [1]. Potyviruses are exclusively transmitted by aphids [3]. Studying the attraction of Rhopalosiphum maidis to Potyvirus infected plants can help better the understanding of plant virus transmission and behavior of aphids, leading to improved pest management processes, and benefitting agriculture as a whole.